A Short-Term Assessment of Lumbar Sagittal Alignment Parameters in Patients Undergoing Anterior Lumbar Interbody Fusion. Issue 23 (1st December 2022) - Lambrechts, Mark J.; Siegel, Nicholas; Karamian, Brian A.; Fredericks, Donald J.; Curran, John; Safran, Jordan; Canseco, Jose A.; Woods, Barrett I.; Kaye, David; Hilibrand, Alan S.; Kepler, Christopher K.; Vaccaro, Alexander R.; et al.
Abstract : Study Design: Retrospective cohort. Objective: To determine if intraoperative on-table lumbar lordosis (LL) and segmental lordosis (SL) coincide with perioperative change in lordosis. Summary of Background Data: Improvements in sagittal alignment are believed to correlate with improvements in clinical outcomes. Thus, it is important to establish whether intraoperative radiographs predict postoperative improvements in LL or SL. Materials and Methods: Electronic medical records were reviewed for patients ≥18 years old who underwent single-level and two-level anterior lumbar interbody fusion with posterior instrumentation between 2016 and 2020. LL, SL, and the lordosis distribution index were compared between preoperative, intraoperative, and postoperative radiographs using paired t tests. A linear regression determined the effect of subsidence on SL and LL. Results: A total of 118 patients met inclusion criteria. Of those, 75 patients had one-level fusions and 43 had a two-level fusion. LL significantly increased following on-table positioning [delta (Δ): 5.7°, P <0.001]. However, LL significantly decreased between the intraoperative to postoperative radiographs at two to six weeks (Δ: −3.4°, P =0.001), while no change was identified between the intraoperative and more than three-month postoperative radiographs (Δ: −1.6°, P =0.143). SL was found to significantly increase from the preoperative to intraoperative radiographs (Δ: 10.9°, P <0.001), but it subsequently decreased at the two to six weeks follow up (Δ: −2.7, P <0.001) and at the final follow up (Δ: −4.1, P <0.001). On linear regression, cage subsidence/allograft resorption was predictive of the Δ SL (β=0.55; 95% confidence interval: 0.16–0.94; P =0.006), but not LL (β=0.10; 95% confidence interval: −0.44 to 0.65; P =0.708). Conclusion: Early postoperative radiographs may not accurately reflect the improvement in LL seen on intraoperative radiographic imaging, but they are predictive of long-term lumbar sagittal alignment. Each millimeter of cage subsidence or allograft resorption reduces SL by 0.55°, but subsidence does not significantly affect LL. Levels of Evidence: 4